EFFECT OF SMALL VIBRATIONS ON STRAIN IN ROCKS AT CONSTANT LOADS - Trapeznikov Yu.A.; Manzhikov B.Ts.; Bogomolov L.M. (My University, 2000)
A long-continued rheologic experiment was conducted to investigate the effects of small mechanical vibrations on strain and acoustic emission (AE) in granite specimens under uniaxial compression. Previous work [4] revealed relations between vibrations and plasticity. The experiment reported here showed variations in the rate of acoustic emission under vibrations, which provides evidence of the effects of small vibrations, not only on plasticity, but also on effects that control failure in specimens, such as stress concentration and relaxation at inhomogeneities. A distinctive feature of the effect of small vibrations consists in a delayed change in AE rate after turning on and off the vibration source. The behavior of the specimen reaction delay time was investigated as a function of a mean load and a loading history.